Sigmoido-vesical fistula secondary to sigmoid colon cancer presenting as urinary tract infection with Lactococcus lactis: A case report - An, Yanhua; Cao, Qiumei; Liu, Yixin; Lei, Luping; Wang, Dawei; Yang, Yanjie; Kong, Weijie; An, Dali; Liu, Dan (Frontiers in Oncology, 2023)
A colovesical fistula is a pathological communication between the colon and bladder. The symptoms include pneumaturia, fecaluria, and a lower urinary tract infection. The diagnosis is based on clinical symptoms, but the symptoms are not specific. Therefore, confirming the diagnosis is challenging. Urine cultures performed in patients with colovesical fistulas usually show growth of Escherichia coli or mixed growth of bowel organisms. Urinary tract infections caused by Lactococcus lactis are very rare, as it is rarely considered pathogenic in humans. We report the case of a 70-year-old woman who presented with symptoms of a recurrent urinary tract infection. Urine cultures were positive for L. lactis. Abdominopelvic computed tomography (CT) revealed focal thickening of the bladder wall and gas in the bladder. Cystoscopic examination and colonoscopy revealed sigmoid colon cancer and a sigmoido-vesical fistula. Laparoscopic surgical treatment was done. The patient recovered and was discharged 3 weeks later without chemoradiotherapy. On follow-up after 6 months, the patient was asymptomatic and stable. To our knowledge, this is the second reported case of L. lactis infection of the urinary tract and the first reported case in adults. L. lactis infection usually indicates the presence of serious underlying diseases such as malignancies, uncontrolled diabetes, and organ failure.